Eco-bricks: a sustainable substitute for construction materials - C. Antico, Federico; J. Wiener, María; Araya-Letelier, Gerardo; Gonzalez Retamal, Raúl (Revista de la Construcción. Journal of Construction, 2017)
Eco-bricks, polyethylene terephthalate (PET) bottles filled with mixed inorganic waste, have become a low cost construction material and a valid recycling method to reduce waste disposal in regions where industrial recycling is not yet available. Because Eco-bricks are filled with mixed recovered materials, potential recycling of its constituents is difficult at the end of its life. This study proposes considering Eco-bricks filled with a single inorganic waste material to work as a time capsule, with potential for recovering the filling material when other ways of waste valorization are available within those communities that currently have no better recycling options. This paper develops an experimental characterization of density, filler content (by volume), thermal shrinkage, elastic modulus and deformation recovery capacity using four different filler materials: 1) PET; 2) paper & cardboard; 3) tetrapack; and 4) metal. Overall, Eco-brick’s density, thermal shrinkage and elastic modulus are dependent on the filler content. Density and elastic modulus of the proposed Eco-bricks are similar to values of medium-high density expanded polystyrene (EPS) used in nonstructural construction, reason why we suggest that these Eco-bricks might be a sustainable alternative to EPS or other nonstructural construction materials.